EVALUASI PENCATATAN LAPORAN KEUANGAN PADA UKM RIZPROD EQUIPMENT SESUAI DENGAN SAK ETAP - Shinta Maharani Trivena (Politeknik Negeri Malang, 2017)
This study aims to analyze and apply financial reporting harmonization made by Rizprod Equipment with SAK ETAP. The type of research used is descriptive research with qualitative approach. The result of the research is financial report made by Rizprod Equipment and the report is not in accordance with SAK ETAP, where the financial statements in accordance with SAK ETAP are minimal. Statements of cash flows, changes in capital, and income statement. This simple financial record is busy and there is no special employee with education background Accounting ready to prepare financial report in accordance with SAK ETAP. In addition, as a result of business actors deem not necessarily financial accountability in detail because all financial statements are made for private consumption so that his assumption is enough by the business owner.